Phosphorus fraction transformation and soil acidity mitigation through integration of water hyacinth biochar with organic and synthetic phosphorus sources in acidic soil - Lewoyehu, Mekuanint; Kohira, Yudai; Addisu, Solomon; Gezahegn, Ashenafei; Wutisirirattanachai, Tassapak; Fentie, Desalew; Sato, Shinjiro (Frontiers in Environmental Science, 2026)
Phosphorus (P) deficiency is a major problem in acidic and tropical soils, including in Ethiopia, because more than 80% of P derived from synthetic fertilizers becomes fixed and unavailable. The short-lived effect of lime and the limited application of fertilizers due to increasing costs cannot solve the problem, leading to significant declines in crop productivity. This study examined how integrating water hyacinth biochar with organic and synthetic P sources affects the transformation of soil P fractions and soil acidity amelioration in Ethiopian soil. We set up a 90-day incubation experiment using P fertilizer, poultry manure (PM), and their pairwise combinations with 1% and 2% biochar and lime, along with a negative control. Soil samples were taken on days 0, 3, 7, 15, 30, 45, 60, and 90 for analyzing pH, exchangeable acidity, exchangeable Al3+, and available P, while samples taken on days 3, 30, and 90 were used to analyze the transformations of P fractions. The results indicated that the efficacy of biochar–fertilizer and biochar–PM integrations outperformed that of fertilizer and PM alone and their combinations with lime, significantly increasing the soil pH by 0.99–1.79 units, available P by 611%–839%, labile P fractions by 1,180%–1,795%, and calcium-associated P by 372%–611%. In contrast, they decreased exchangeable acidity by 80.0%–95.7%, exchangeable Al3+ by 92.5%–100%, Al/Fe-bound P fractions by 35%–60%, and recalcitrant P by 18%–20% compared with the control after incubation. More importantly, co-application of 2% biochar with PM and fertilizer eliminated exchangeable Al3+. Overall, biochar–PM combinations exhibited better efficacy compared to biochar–fertilizer counterparts. Therefore, it can be concluded that valorizing invasive water hyacinth into biochar and co-applying it with organic and synthetic P fertilizers can be an integrated strategy for repurposing waste to address soil acidity and P deficiency, enhance soil fertility, and reduce reliance on fertilizers, thereby promoting sustainable agriculture and effective waste management.